Audit Lingkungan atas Kepatuhan K3, Manajemen Risiko, dan Kesehatan Lingkungan pada Puskesmas Tenggilis - Syahna Shinta Yunari; Cholis Hidayati (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
This studyyaims tooevaluate environmental activities at the Tenggilis Community Health Center by assessing compliance with occupational health and safety, risk management, and environmental health aspects. The method used is descriptiveequalitative with dataacollection through questionnaires, observation,iinterviews, andddocumentation. The analysis was conducted through reduction, presentation, and conclusion drawing. The results of the study show that the Tenggilis Community Health Center has generally met the criteria in each aspect, buttthere are still someeshortcomings. Innthe OSH aspect, training needs to be scheduled immediately. In risk management, all policies need to beeupdated to include the name and signature of theenew head offthe CommunityyHealth Center. In the environmental health aspect, deficiencies were found relateddto the completeness offthe administration of technical approval for wastewater quality standards and permits for B3 waste storage and wastewater treatment plants, which must be resolved immediately.